Thermal Power Plants Hybrid Heat Supply Technology for Low-Temperature Heat Source Enhancement Economic Analysis - Xu, Haoran; Jiang, Chengan; Xu, Chengfei; Jiang, Yanni (Transactions on Environment, Energy and Earth Sciences, 2024)
To solve the defects of insufficient heating capacity and high energy cost in the traditional heating mode of the thermal power plant, two 300 MW pumped-condensing air-cooled heating units are retrofitted by adopting a high backpressure operation mode and utilizing the low-temperature heat source quality-improving hybrid heating technology. It is found that when the load is 210 MW and the operating back pressure is 45 kPa and 54 kPa after the retrofit, the consumption of standard coal for every 1 GJ of heat is 8.19 kg and 9.76 kg, which is 16.81 kg and 15.24 kg less than that of the traditional heat supply method. When the load is 250 MW and the operating back pressure is 45 kPa, the consumption of standard coal is 8.65 kg per GJ of heat supplied, which is 16.35 kg less than that of the traditional heating method. The ROI of the retrofit is 49.01%, with a payback period of about 2.04 years, after which it can bring an annual profit of 24.5504 million RMB per year to the power plant. It can reduce the emission of soot by 152.17 t, carbon dioxide by 82.17 t, sulfur dioxide by 258.68 t, and nitrogen oxides by 225.20 t per year. Therefore, this transformation is a green and efficient, energy-saving, and environmentally friendly technology with high economic returns and good prospects, providing a way of thinking about the new heating technology of the power plant.